RCM (RELIABILITY CENTERED MAINTENANCE): THE IMPLEMENTATION IN PREVENTIVE MAINTENANCE (CASE STUDY IN AN EXPEDITION COMPANY) - Fathurohman Fathurohman; Slamet Triyono (EKOMABIS: Jurnal Ekonomi Manajemen Bisnis, 2020)
Expedition truck is a vehicle that serves to transfer goods from one place to another. Previously maintenance policy was periodic, depending on the run distance and Run To Failure, maintain the trucks after the occurrence of component damage then system failure. Analysis in maintenance management based on system and critical components do optimize truck performance by using RCM (Reliability Centered Management) method. There are 5 systems in a truck: electrical system, power steering system, cooling machine system, coupling system, and brake system. Interaction and function of the components from each system are analyzed, evaluated the failure mode (FMEA method), and categorized the level of critical damage and adjusted the maintenance time (LTA method). The results of the RCM method for 16 component functions from the 5 systems are 5 component functions with Time Directed (TD), 6 Condition Directed (CD), 3 Failure Finding (FF), and 2 component functions by Run To Failure (RTF).